BOLD responses to negative reward prediction errors in human habenula - Salas, Ramiro; Baldwin, Philip; De Biasi, Mariella; Montague, Read (Frontiers in Human Neuroscience, 2010)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Although positive reward prediction error, a key element in learning that is signaled by dopamine cells has been extensively studied, little is known about negative reward prediction errors in humans. Detailed animal electrophysiology shows that the habenula, an integrative region involved in many processes including learning, reproduction, and stress responses, also encodes negative reward-related events such as negative reward prediction error signals. In humans, however, the habenula's extremely small size has prevented direct assessments of its function. We developed a method to functionally locate and study the habenula in humans using fMRI, based on the expected reward-dependent response phenomenology of habenula and striatum. We provide conclusive evidence for activation in human habenula to negative reward prediction errors.